In situ evaluation of cytotoxic immune response in central nervous system of human rabies transmitted by dog and vampire bat - Guedes, F.; Fernandes, E. R.; Martins, J. F.; Pagliari, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Introduction: CD8 (+) T cells and natural killer (NK) cells are immune effectors that, by cytokine production or cytotoxicity, help to contain a viral infection. Objective: To quantify and compare the T CD8 lymphocytes, natural killer cells and B granzyme expression in central nervous system lesions of human rabies transmitted by dog and vampire bat.